Method for preparing porous carbon structure containing sub-nanoscale ionic conduction improvement layer by using atomic layer deposition and application of porous carbon structure

By depositing a sub-nanoscale ion conduction improvement layer on the porous carbon substrate, the problems of poor interface misfit and bonding force of silicon-carbon composite anode material during charge and discharge are solved, and the effect of improving rate performance and cyclic stability is achieved.

CN119695060APending Publication Date: 2025-03-25SUN YAT SEN UNIV

Patent Information

Application Number
CN202411850630.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the prior art, silicon-carbon composite anode material has interface misfit and poor bonding force during charging and discharging, resulting in silicon particles being easily shedded during volume changes, resulting in capacity loss.

Method used

A sub-nanoscale ion conduction improvement layer, such as lithium aluminum phosphate, is deposited on a porous carbon substrate by atomic layer deposition method, improving the interface affinity and ion transport efficiency between silicon and carbon.

Benefits of technology

It effectively reduces the polarization of the silicon-carbon negative electrode during the charging and discharging process, improves the rate performance, and solves the problem of low ion transmission efficiency between silicon and carbon, and improves the cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695060A_ABST
    Figure CN119695060A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery materials, and particularly relates to a method for preparing a porous carbon structure containing a sub-nanoscale ionic conduction improvement layer by utilizing atomic layer deposition and application. The invention discloses a porous carbon-silicon negative electrode structure, which is characterized in that a sub-nano-scale ion conduction improvement layer is added between a porous carbon substrate and silicon particles, and the sub-nano-scale ion conduction improvement layer comprises silicon carbide, aluminum phosphide, aluminum nitride, aluminum oxide, lithium phosphate, aluminum phosphate and lithium aluminum phosphate. Meanwhile, the invention also discloses a preparation method of the porous carbon-silicon negative electrode structure, namely, a sub-nano-scale ion conduction improvement layer is deposited on the porous carbon substrate through an atomic layer deposition method, so that the binding force between the sub-nano-scale ion conduction improvement layer and silicon particles and an ion transport channel are increased, and the ion conduction of a vapor deposition silicon-carbon negative electrode material is improved; the polarization of the material is effectively reduced, so that the rate capability of the battery is improved, and the cycling stability of the porous carbon structure battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a method and application of preparing a porous carbon structure containing a sub-nanometer scale ion conduction improvement layer by atomic layer deposition. Background Art

[0002] At present, the most effective way to prepare silicon-carbon composite negative electrode materials is to use the high specific capacity of silicon materials and the stability of carbon materials. Among the many silicon-carbon composite negative electrode material preparation processes, the silicon-carbon composite negative electrode prepared by chemical vapor deposition (CVD) has attracted widespread attention due to its advantages such as high charge and discharge efficiency, good cycle stability, low equipment requirements, and suitability for industrial production. The core of this technology is to store silicon through a porous carbon skeleton. Generally, silicon is deposited on the inner surface of porous carbon by CVD. Porous carbon can provide an electronic conductive network for silicon, and at the same time, the voids inside the porous carbon are used to buffer the volume expansion of silicon during lithium insertion, thereby achieving good cycle stability. However, for vapor-deposited silicon-carbon, the deposition thickness is difficult to quantify, and it is easy to completely block the nano-scale micropores in the porous carbon, resulting in less space for silicon to sink; in addition, the bonding force between the porous carbon substrate and silicon is poor. When silicon undergoes a huge volume change during the charge and discharge process, the active material silicon is easy to fall off from the porous carbon substrate, and the detached silicon will lose its electrochemical activity due to being separated from the electronic conductive network constructed by the carbon substrate, which ultimately leads to the capacity loss of the negative electrode material. Therefore, Si-C interface modification plays a vital role.

[0003] At present, how to improve the interface incompatibility between silicon and porous carbon, strengthen the bonding between silicon and porous carbon, and improve the electrochemical performance of silicon-carbon negative electrodes are technical problems that technicians in this field need to solve urgently. However, the research on silicon-carbon interface modification is mainly aimed at silicon-carbon composite materials prepared by sacrificial template method, magnesium thermal reduction method, etc., but no technicians have studied how to modify the silicon-carbon interface in the field of atomic layer deposition of silicon-carbon. Summary of the invention

[0004] In order to overcome the shortcomings of the above-mentioned prior art, the present invention deposits a sub-nanoscale ion conduction improvement layer on a porous carbon substrate by atomic layer deposition, thereby effectively reducing the polarization of the silicon-carbon negative electrode during the charge and discharge process, improving its rate performance, and solving the problem of low ion transfer efficiency between silicon and carbon in the carbon-silicon negative electrode structure.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] The first aspect of the present invention provides a porous carbon silicon negative electrode structure, which includes a porous carbon substrate, silicon particles and a sub-nanoscale ion conduction improvement layer in the middle layer, and the sub-nanoscale ion conduction improvement layer is coated on the surface of the porous carbon substrate; the sub-nanoscale ion conduction improvement layer includes silicon carbide, aluminum phosphide, aluminum nitride, aluminum oxide, lithium phosphate, aluminum phosphate, and lithium aluminum phosphate.

[0007] The sub-nanometer scale ion conduction improvement layer and the porous carbon substrate both have interface affinity; and the lithium phosphate in the sub-nanometer scale ion conduction improvement layer can improve the lithium ion conductivity. The sub-nanometer scale ion conduction improvement layer is coated on the surface of the porous carbon substrate, and the thickness of the sub-nanometer scale ion conduction improvement layer coated on each surface area of ​​the porous carbon substrate is uniformly distributed.

[0008] Preferably, the sub-nanoscale ion conduction improving layer is lithium aluminum phosphate.

[0009] The second aspect of the present invention provides a method for preparing the porous carbon-silicon negative electrode structure of the first aspect, the method comprising the following steps:

[0010] S11: providing a porous carbon substrate;

[0011] S12: introducing a gaseous precursor and depositing a lithium aluminum phosphate film on the surface of the porous carbon substrate by atomic layer deposition, specifically including steps S121 to S1211. In steps S121 to S1210, nitrogen is used as a carrier gas at a flow rate of 5 to 200 sccm:

[0012] S121: Laying out base materials, laying out tert-butyl lithium in a tert-butyl lithium tank, laying out trimethyl phosphate in a trimethyl phosphate cylinder, laying out trimethyl aluminum in a trimethyl aluminum cylinder, and laying out a porous carbon substrate in a reaction chamber;

[0013] S122: heating the equipment, heating the initial temperature of tert-butyl lithium to 120°C, and the initial temperature of trimethyl phosphate to 45°C; heating the initial temperature of the reaction chamber to 100-500°C, heating the initial temperature of the transport pipeline and the ALD pulse valve to 180°C, and evacuating the reaction chamber and the transport pipeline to a pressure of 5-500Pa;

[0014] S123: After applying the lithium source and the ALD system is evenly heated, the ALD pulse valve at the tert-butyl lithium tank is opened for 300 to 3000 ms to allow the tert-butyl lithium to enter the reaction chamber, undergo self-saturated adsorption and exchange reaction with the surface of the substrate to be plated, and generate a lithium-substituted substrate;

[0015] S124: cleaning the residual material, introducing an inert gas pulse into the reaction chamber to clean the tert-butyl lithium that has not reacted completely and the by-products generated by the reaction;

[0016] S125: Reduction reaction, opening the ALD pulse valve at the trimethyl phosphate cylinder for 20 to 1000 ms, so that the trimethyl phosphate enters the reaction chamber in the gas phase, chemically adsorbs and reacts with the surface of the lithium-substituted base material, and generates a lithium phosphate thin film blank;

[0017] S126: Cleaning the film, introducing an inert gas pulse into the reaction chamber to clean the phosphoric acid source that has not reacted completely and the byproducts generated by the reaction, and then generating a single-layer atomic layer deposited lithium phosphate film through self-saturation;

[0018] S127: Open the ALD pulse valve at the trimethyl aluminum cylinder for 20 to 1000 ms to allow trimethyl aluminum to enter the reaction chamber in gas phase and chemically adsorb and react with the surface of the lithium phosphate film to generate an aluminum-based replacement base material;

[0019] S128: Cleaning the membrane, introducing an inert gas pulse into the reaction chamber to clean the unreacted phosphoric acid source and the by-products generated by the reaction;

[0020] S129: Reduction reaction, opening the ALD pulse valve at the trimethyl phosphate cylinder for 20 to 1000 ms, so that the trimethyl phosphate enters the reaction chamber in the gas phase, chemically adsorbs and reacts with the surface of the aluminum replacement base material, and generates a lithium aluminum phosphate thin film blank;

[0021] S1210: Cleaning and film formation, introducing an inert gas pulse into the reaction chamber to clean the unreacted phosphoric acid source and the byproducts generated by the reaction, and then generating a double-layer atomic layer deposited lithium aluminum phosphate film through self-saturation;

[0022] S13: performing multilayer deposition, repeating the process cycle of step S121 to step S1210 on the lithium aluminum phosphate thin film material obtained by the double-layer atomic layer deposition, and stacking another lithium aluminum phosphate thin film on the lithium aluminum phosphate thin film material, while controlling the total thickness of the lithium aluminum phosphate thin film to not more than 2 nm;

[0023] S14: using the modified substrate material of S13 in a subsequent silicon deposition step to prepare a modified vapor-deposited silicon-carbon material.

[0024] The present invention uses tert-butyl lithium as a lithium source agent, as a metal organic compound precursor, to undergo chemical self-saturation adsorption and exchange reaction with the surface of the base material to be plated, and generates a lithium replacement precursor on the surface of the porous carbon substrate. The lithium replacement precursor then undergoes a reduction reaction with the gas phase precursor trimethyl phosphate and the gas phase precursor trimethylaluminum to generate a double-layer lithium aluminum phosphate film. Among them, the initial heating temperature of the tert-butyl lithium is 120°C, the trimethyl phosphate and the trimethylaluminum are reducing agents, and the initial heating temperature of the trimethyl phosphate is 45°C; the reaction temperature of the reaction chamber is 100-500°C, and the operating temperature of the transport pipeline and the ALD pulse valve is 180°C to ensure that the precursor source is transported in the gas phase without condensation.

[0025] Preferably, in S13, the total thickness of the lithium aluminum phosphate film is controlled to be no more than 1 nm.

[0026] Preferably, in steps S121 to S1210 , nitrogen is used as the carrier gas with a flow rate of 5 to 100 sccm.

[0027] Preferably, in step S122, the initial temperature of the reaction chamber is heated to 150-300°C, and the reaction chamber and the transport pipeline are evacuated to a pressure of 10-200Pa.

[0028] Preferably, in step S123, the ALD pulse valve at the tert-butyl lithium tank is opened for 500 to 2000 ms.

[0029] Preferably, in step S125, the ALD pulse valve at the trimethyl phosphate cylinder is opened for 50 to 500 ms.

[0030] Preferably, in step S127, the ALD pulse valve at the trimethyl aluminum cylinder is opened for 50 to 500 ms.

[0031] Preferably, in step S129, the ALD pulse valve at the trimethyl phosphate cylinder is opened for 50 to 500 ms.

[0032] The third aspect of the present invention further provides a battery, comprising the porous carbon silicon negative electrode structure described in the first aspect.

[0033] The porous carbon structure including the sub-nanometer scale ion conduction improvement layer provided by the present invention is provided by adding a sub-nanometer scale ion conduction improvement layer with controllable thickness on the porous carbon substrate as the sub-nanometer scale ion conduction improvement layer with affinity for the interface between silicon and carbon. Since these sub-nanometer scale ion conduction improvement layers (such as lithium phosphate) can improve the lithium ion conduction efficiency, the polarization of the negative electrode during the charge and discharge process is effectively reduced, and the rate performance of the negative electrode is further improved. At the same time, since the thickness of the contained sub-nanometer scale ion conduction improvement layer can be controlled to be no more than 2nm, the introduction of the sub-nanometer scale ion conduction improvement layer of appropriate thickness only expands more electron channels and ion channels, so the effect on the first cycle coulomb efficiency of the negative electrode is very small, and no obvious capacity loss is caused. Therefore, the porous carbon structure including the sub-nanometer scale ion conduction improvement layer provided by the present invention improves the cycle stability of the porous carbon structure battery under the condition of ensuring that the capacity is not lost.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] The present invention discloses a porous carbon silicon negative electrode structure, wherein a sub-nanometer scale ion conduction improvement layer is introduced between a porous carbon substrate and silicon particles, wherein the sub-nanometer scale ion conduction improvement layer comprises silicon carbide, aluminum phosphide, aluminum nitride, aluminum oxide, lithium phosphate, aluminum phosphate, and lithium aluminum phosphate. At the same time, a preparation method of the porous carbon silicon negative electrode structure is also provided, namely, a sub-nanometer scale ion conduction improvement layer is deposited on a porous carbon substrate by an atomic layer deposition method, and the porous carbon substrate is bonded with the sub-nanometer scale ion conduction improvement layer, thereby increasing the bonding force between the porous carbon substrate and the silicon particles and the ion transport channel, and solving the problem of low ion transmission efficiency between silicon and carbon in the carbon silicon negative electrode structure, so that the porous carbon structure improves the cycle stability of the porous carbon structure battery under the condition of ensuring that the capacity is not lost.

[0036] In addition, taking lithium aluminum phosphate as an example, the present invention also provides a method for preparing a porous carbon structure containing a sub-nanometer scale ion conduction improvement layer by atomic layer deposition, using atomic layer deposition technology, using carrier gas flow to pulse tert-butyl lithium into a vacuum reaction chamber to undergo chemical self-saturation adsorption with a porous carbon substrate, and an exchange reaction occurs, thereby generating a lithium replacement precursor on the pore surface of the porous carbon substrate, and then the lithium replacement precursor is reduced with trimethyl phosphate and trimethylaluminum, respectively, to generate a single-layer aluminum phosphate film and a single-layer lithium phosphate film. Since the chemical adsorption of the precursor is self-saturating, a double-layer lithium aluminum phosphate thin layer deposition can be completed in one process cycle, and then each time a process cycle is repeated, a double-layer lithium aluminum phosphate film can be superimposed on the upper layer of the previous double-layer lithium aluminum phosphate film material, and then the thickness of the lithium aluminum phosphate film can be accurately controlled by controlling the number of process cycles. The technical solution provided by the present invention modifies the inner wall of the porous carbon with a sub-nano / nanoscale ion conduction improvement layer (such as a lithium aluminum phosphate coating layer), thereby improving the ion conduction of the vapor-deposited silicon-carbon negative electrode material and effectively reducing the polarization of the material, thereby improving the rate performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 A process flow chart of a carbon-silicon anode structure including a sub-nanometer scale ion conduction improvement layer;

[0038] Figure 2 The SEM test results of porous carbon with different thickness of aluminum phosphate lithium ion conduction improvement layer;

[0039] Figure 3 Comparison of the rate performance of silicon-carbon batteries made with aluminum phosphate lithium ion conduction improvement layers of different thicknesses. DETAILED DESCRIPTION

[0040] The specific embodiments of the present invention are further described below. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0041] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are commercially available unless otherwise specified.

[0042] For traditional coated Si / C materials (C coated on Si surface), the middle layer is generally SiO2 or SiO x However, during the formation of the intermediate layer, due to the magnesium thermal reduction of SiO2 to prepare Si, some SiO2 or SiO xRemains in Si; in the subsequent carbon deposition process, carbon will be directly deposited on SiO2 or SiO x On the middle layer. Some researchers have also introduced heteroatoms (N, O, S, P, etc.) into the carbon coating layer. The doped elements are conducive to building a tighter and more stable interface between silicon and carbon. Moreover, this magnesium thermal reaction is only applicable to the negative electrode material structure in which silicon is prepared first and then carbon is deposited, that is, the negative electrode material with carbon coated on the silicon surface. As for the negative electrode material structure formed by depositing carbon particles on a porous carbon substrate, the technical means commonly used by those skilled in the art are: silicon is deposited on the surface of a porous carbon substrate by vapor deposition to form a negative electrode material. However, there is currently no research on the introduction of an intermediate layer in this field. Therefore, in the silicon-coated carbon structure formed by vapor deposition of silicon, the bonding force between the silicon particles and the porous carbon substrate and the conduction efficiency between the particles still need to be improved.

[0043] In view of this, the present invention further studies the structure of the porous carbon surface, and based on the preparation method of atomic layer deposition carbon particles, a sub-nanoscale ion conduction improvement layer with a thickness of less than 1 nm is first deposited on the porous carbon substrate by atomic layer deposition before vapor deposition of silicon particles; since the thickness of the intermediate layer formed by the atomic layer method is controllable and the composition is uniform, more ion channels can be provided between the porous carbon substrate and the silicon particles, thereby improving the conduction rate, thereby ensuring the voltage loss caused by polarization during the charge and discharge process, and improving its electrochemical performance; and the uniform distribution of the sub-nanoscale ion conduction improvement layer in the porous carbon substrate also improves the interface effect.

[0044] Specifically, the first aspect of the present invention provides a carbon-silicon negative electrode structure including a sub-nanometer scale ion conduction improvement layer, comprising:

[0045] (1) Porous carbon substrate: The porous carbon substrate may include a variety of sources, including but not limited to biomass charcoal (lychee trunks, waste coffee grounds, rice husks, etc.), synthetic polymers, natural polymers, etc. The pores of the porous carbon may include micropores, mesopores and macropores. For example, the porous carbon may be selected from MRP16, MRP18, MRP20, and MSP-X of Changzhou Chuangming Super Electric Material Technology Co., Ltd.

[0046] (2) Silicon particles;

[0047] (3) Ion conduction improvement layer; the ion conduction improvement layer has interface affinity with the silicon particles, and with the porous carbon substrate. The ion conduction improvement layer is coated on the surface of the porous carbon substrate, and the silicon particles are bonded to the surface of the porous carbon substrate through the sub-nanometer scale ion conduction improvement layer, and the thickness of the sub-nanometer scale ion conduction improvement layer coated on each surface area of ​​the porous carbon substrate is uniformly distributed. An inorganic intermediate layer with interface affinity is introduced between silicon and porous carbon by atomic layer deposition, but an excessively thick intermediate layer will seriously occupy the space for silicon particle deposition, so the thickness of the intermediate layer must be strictly controlled, generally not exceeding 1 nm. The method of the present invention is to deposit directly on a porous carbon substrate, and the deposited intermediate layer is uniform and has a controllable thickness. It can build a firm particle transmission interface with the subsequently deposited silicon without hindering the deposition of silicon particles, thereby significantly improving the electrochemical performance. In order to demonstrate the criticality of the thickness of the inorganic intermediate layer, the present invention sets up multiple embodiments in which the thickness of the sub-nanometer scale ion conduction improvement layer is less than 1nm to demonstrate the preferred thickness range; because the study found that the more sub-nanometer scale ion conduction improvement layers are introduced, the more they will occupy the silicon particle deposition space, thereby affecting the electrochemical performance of the material (especially the battery capacity), so it is not recommended to deposit a thickness greater than 1nm. Therefore, the present invention is based on the study and comprehensive consideration of the bonding force between silicon and the porous carbon substrate and the influence of the sub-nanometer scale ion conduction improvement layer on the electrochemical performance of the negative electrode material. After repeated experiments, the above-mentioned preferred thickness range of the sub-nanometer scale ion conduction improvement layer is obtained.

[0048] In addition, the present invention examines a large number of chemical substances that may have good adhesion between the porous carbon substrate and the silicon particles. After repeated calculations of the adhesion force and repeated experiments and verifications, it is found that when the ion conduction improvement layer is aluminum phosphide, aluminum nitride, aluminum oxide, lithium phosphate, aluminum phosphate or lithium aluminum phosphate, it can have good adhesion between the porous carbon substrate and the silicon particles. Therefore, it is concluded that the above-mentioned substances can be used as suitable sub-nanoscale ion conduction improvement layers.

[0049] The second aspect of the present invention also provides a method for preparing the carbon-silicon negative electrode structure comprising a sub-nanometer scale ion conduction improvement layer, such as Figure 1 As shown, the specific steps include:

[0050] S11: providing a porous carbon substrate;

[0051] S12: introducing a gaseous precursor and using an atomic layer deposition method to cause chemical self-saturation adsorption on the surface of the porous carbon substrate, so that a sub-nanometer scale ion conduction improvement layer with a uniform thickness distribution is formed in various regions on the surface of the porous carbon substrate.

[0052] S13: Repeat S12 to perform multi-layer deposition.

[0053] S14: forming multiple sub-nanometer scale ion conduction improvement layers with uniform thickness distribution in various regions on the surface of the porous carbon substrate, so as to achieve precise modification of the inner and outer surfaces of the porous carbon with fast ion conductors.

[0054] S15: using the modified material in a subsequent silicon deposition step to prepare a modified vapor-deposited silicon-carbon material.

[0055] The thickness of the sub-nanoscale ion conduction improvement layer coated on each surface area of ​​the porous carbon substrate is evenly distributed; and there is interface affinity between the sub-nanoscale ion conduction improvement layer and the porous carbon substrate.

[0056] The detailed conditions of the atomic layer deposition process (such as temperature, pressure, gas flow, etc.) will be adjusted according to the specific compounds to be deposited and the material thickness sought. Each material and compound has its own specific deposition parameters to ensure the quality and characteristics of the deposit. At the same time, after repeated experiments in the present invention, the conditions for preparing the aforementioned various sub-nanometer scale ion conduction improvement layers by atomic layer deposition have been obtained, and then a uniformly distributed sub-nanometer scale ion conduction improvement layer can be prepared, and the thickness of the obtained sub-nanometer scale ion conduction improvement layer is a controllable ideal thickness. Taking the compound of the ion conduction improvement layer using lithium aluminum phosphate as an example, the preparation process conditions of different sub-nanometer scale ion conduction improvement layers, the preferred experimental conditions and the specific preparation process are described as follows:

[0057] Step S12, forming a sub-nanometer scale ion conduction improvement layer on the surface of the porous carbon substrate by atomic layer deposition, specifically comprising steps S121 to S1211:

[0058] Step S121: Laying out base materials (packaging), laying out lithium source agent in tert-butyl lithium tank, laying out trimethyl phosphate in trimethyl phosphate cylinder, laying out trimethyl aluminum in trimethyl aluminum cylinder, and laying out porous carbon substrate in reaction chamber;

[0059] Step S122: The equipment is heated to heat the initial temperature of tert-butyl lithium to 120°C, and the initial temperature of trimethyl phosphate to 45°C; the initial temperature of the reaction chamber is heated to 100-500°C, the initial temperature of the transport pipeline and the ALD pulse valve is heated to 150-200°C, and the reaction chamber and the transport pipeline are evacuated to a pressure of 5-500Pa;

[0060] Step S123: After applying the lithium source and the ALD system is evenly heated, the ALD pulse valve at the tert-butyl lithium tank is opened for 300 to 3000 ms to allow the tert-butyl lithium to enter the reaction chamber, undergo self-saturated adsorption and exchange reaction with the surface of the substrate to be plated, and generate a lithium-substituted substrate;

[0061] Step S124: cleaning the remaining material, introducing an inert gas pulse into the reaction chamber to clean the unreacted tert-butyl lithium and the by-products generated by the reaction;

[0062] Step S125: reduction reaction, opening the ALD pulse valve at the trimethyl phosphate cylinder for 20 to 1000 ms, allowing the trimethyl phosphate to enter the reaction chamber in the gas phase, chemically adsorb and react with the surface of the lithium-substituted base material, and generate a lithium phosphate thin film blank;

[0063] Step S126: Cleaning the film, introducing an inert gas pulse into the reaction chamber to clean the unreacted phosphoric acid source and the byproducts generated by the reaction, and then forming a single-layer atomic layer deposited lithium phosphate film through self-saturation;

[0064] Step S127: Open the ALD pulse valve at the trimethyl aluminum cylinder for 20 to 1000 ms to allow trimethyl aluminum to enter the reaction chamber in gas phase and chemically adsorb and react with the surface of the lithium phosphate film to generate an aluminum-based replacement base material;

[0065] Step S128: Cleaning the membrane, introducing an inert gas pulse into the reaction chamber to clean the unreacted phosphoric acid source and the by-products generated by the reaction;

[0066] Step S129: reduction reaction, opening the ALD pulse valve at the trimethyl phosphate cylinder for 20 to 1000 ms, allowing the trimethyl phosphate to enter the reaction chamber in the gas phase, chemically adsorb and react with the surface of the aluminum replacement base material, and generate a lithium aluminum phosphate thin film blank;

[0067] Step S1210: Cleaning the film, introducing an inert gas pulse into the reaction chamber to clean the unreacted phosphoric acid source and the byproducts generated by the reaction, and then generating a double-layer atomic layer deposited lithium aluminum phosphate film through self-saturation;

[0068] Step S1211: multilayer deposition, repeating the process cycle of step S121 to step S1210 on the lithium aluminum phosphate thin film material obtained by the double-layer atomic layer deposition, and stacking another lithium aluminum phosphate thin film on the lithium aluminum phosphate thin film material obtained by the double-layer atomic layer deposition. Wherein, nitrogen is used as a carrier gas in steps S121 to step S1210, and the flow rate is 5 to 200 sccm. By controlling the number of cycles, the thickness of the lithium aluminum phosphate film is precisely controlled.

[0069] Preferably, in step S122, the initial temperature of the reaction chamber is heated to 150-300°C, and the reaction chamber and the transport pipeline are evacuated to a pressure of 10-200Pa.

[0070] Preferably, in step S123, the ALD pulse valve at the tert-butyl lithium tank is opened for 500 to 2000 ms.

[0071] Preferably, in step S125, the ALD pulse valve at the trimethyl phosphate cylinder is opened for 50 to 500 ms.

[0072] Preferably, in step S127, the ALD pulse valve at the trimethyl aluminum cylinder is opened for 50 to 500 ms.

[0073] Preferably, in step S129, the ALD pulse valve at the trimethyl phosphate cylinder is opened for 50 to 500 ms.

[0074] Preferably, in step S121 to step S1210, nitrogen is used as the carrier gas with a flow rate of 5 to 100 sccm.

[0075] The present invention is further described in detail below in conjunction with Examples 1-3 and Comparative Examples:

[0076] Example 1: A carbon-silicon negative electrode structure including a sub-nanometer scale ion conduction improvement layer and a preparation method thereof

[0077] The sub-nanometer scale ion conduction improvement layer selected is: lithium aluminum phosphate; the lithium aluminum phosphate film is deposited on the porous carbon substrate by atomic layer deposition (the ALD equipment used is Yunlong-LAY-500G ALD), and then silicon particles are deposited on the surface of the sub-nanometer scale ion conduction improvement layer by vapor deposition.

[0078] (1) Depositing a lithium aluminum phosphate film on a porous carbon substrate (porous carbon MRP16 purchased from Changzhou Chuangming Super Electric Material Technology Co., Ltd.), specifically comprising the following steps:

[0079] Step S121: placing a lithium source in a tert-butyl lithium tank, placing trimethyl phosphate in a trimethyl phosphate cylinder, placing trimethyl aluminum in a trimethyl aluminum cylinder, and placing a porous carbon substrate in a reaction chamber;

[0080] Step S122: heating the equipment, heating the initial temperature of tert-butyl lithium to 120°C, and the initial temperature of trimethyl phosphate to 45°C; heating the initial temperature of the reaction chamber to 200°C, heating the initial temperature of the transport pipeline and the ALD pulse valve to 180°C, and evacuating the reaction chamber and the transport pipeline to a pressure of 1000Pa;

[0081] Step S123: After the ALD system is evenly heated, the ALD pulse valve at the tert-butyl lithium tank is opened for 800ms to allow the tert-butyl lithium to enter the reaction chamber, undergo self-saturated adsorption and exchange reaction with the surface of the substrate to be plated, and generate a lithium-substituted substrate;

[0082] Step S124: introducing an inert gas pulse into the reaction chamber to clean the unreacted tert-butyl lithium and the by-products generated by the reaction;

[0083] Step S125: opening the ALD pulse valve at the trimethyl phosphate cylinder for 200 ms, so that the trimethyl phosphate enters the reaction chamber in the gas phase, chemically adsorbs and reacts with the surface of the lithium-substituted base material, and generates a lithium phosphate thin film blank;

[0084] Step S126: introducing an inert gas pulse into the reaction chamber to clean the unreacted phosphoric acid source and the byproducts generated by the reaction, thereby generating a single-layer atomic layer deposited lithium phosphate film through self-saturation;

[0085] Step S127: Open the ALD pulse valve at the trimethyl aluminum cylinder for 200 ms to allow trimethyl aluminum to enter the reaction chamber in gas phase, chemically adsorb and react with the surface of the lithium phosphate film to generate an aluminum-based replacement base material;

[0086] Step S128: introducing an inert gas pulse into the reaction chamber to clean the unreacted phosphoric acid source and the byproducts generated by the reaction;

[0087] Step S129: opening the ALD pulse valve at the trimethyl phosphate cylinder for 200 ms, so that the trimethyl phosphate enters the reaction chamber in the gas phase, chemically adsorbs and reacts with the surface of the aluminum-substituted base material, and generates a lithium aluminum phosphate thin film blank;

[0088] Step S1210: introducing an inert gas pulse into the reaction chamber to clean the unreacted phosphoric acid source and the byproducts generated by the reaction, thereby generating a double-layer atomic layer deposited lithium aluminum phosphate film through self-saturation;

[0089] (2) Repeat step (1) to deposit a second layer until two layers of lithium aluminum phosphate are deposited, and the total thickness is about 0.4 nm;

[0090] (3) Depositing silicon particles on the surface of the sub-nanoscale ion conduction improvement layer; specifically: heating the fluidized bed equipment (FB-CVD-20) to 480°C, introducing silane (such as SiH4) and nitrogen, with nitrogen as the carrier gas, the silane flow rate being 3 L / min, and the nitrogen flow rate being 15 L / min. After 200 minutes of deposition, the silane flow is turned off, the equipment is heated to 580°C, acetylene is introduced, the acetylene flow rate is 3 L / min, and the nitrogen flow rate remains unchanged. After 93 minutes of deposition, the equipment is cooled naturally.

[0091] Example 2: A carbon-silicon negative electrode structure including a sub-nanometer scale ion conduction improvement layer and a preparation method thereof

[0092] Steps (1) and (3) are the same as those in Example 1, except that step (2) is to repeat step (1) to deposit a second layer until five layers of lithium aluminum phosphate are deposited, at which point the total thickness is about 0.6 nm.

[0093] Example 3: A carbon-silicon negative electrode structure including a sub-nanometer scale ion conduction improvement layer and a preparation method thereof

[0094] Steps (1) and (3) are the same as those in Example 1, except that step (2) is to repeat step (1) to deposit a second layer until ten layers of lithium aluminum phosphate are deposited, at which point the total thickness is about 1.0 nm.

[0095] Comparative Example 1: No sub-nanometer ion conduction improvement layer, using vapor deposition deposition method to deposit silicon particles on a porous carbon substrate to prepare a carbon-silicon negative electrode structure

[0096] The specific process steps are as follows:

[0097] (1) providing a porous carbon substrate;

[0098] (2) Silicon is deposited on the porous carbon substrate by vapor deposition, specifically: the fluidized bed apparatus (FB-CVD-20) is heated to 480°C, silane (such as SiH4) and nitrogen are introduced, nitrogen is used as a carrier gas, the silane flow rate is 3 L / min, and the nitrogen flow rate is 15 L / min. After 200 minutes of deposition, the silane introduction is turned off, the apparatus is heated to 580°C, acetylene is introduced, the acetylene flow rate is 3 L / min, and the nitrogen flow rate remains unchanged. After 93 minutes of deposition, the apparatus is naturally cooled.

[0099] Experimental example: Characterization of carbon-silicon anode structure and electrochemical performance test

[0100] The carbon silicon negative electrode structures prepared in Examples 1 to 3 and Comparative Example 1 were subjected to BET tests and SEM tests.

[0101] At the same time, in order to further study the cycle stability of the negative electrode material, the carbon-silicon negative electrode structure containing the ion conduction improvement layer obtained in Examples 1 to 3 was mixed with commercial graphite, and the mixing mass ratio was C-Si:graphite (graphite) = 20:80; and the prepared composite negative electrode material was subjected to an electrochemical performance test, and the negative electrode structure obtained in Comparative Example 1 was also subjected to an electrochemical performance test, and the first cycle charge and discharge curves of the composite negative electrode materials of Comparative Example 1 and Examples 1 to 3 at different rates were obtained, as shown in Table 1, Figure 2 , Figure 3 shown.

[0102] Table 1 Figure 2 , Figure 3 The corresponding BET test results of porous carbon with different thickness of aluminum phosphate lithium ion conduction improvement layer, SEM test results of porous carbon with different thickness of aluminum phosphate lithium ion conduction improvement layer, and rate performance comparison of silicon-carbon batteries made of different thickness of aluminum phosphate lithium ion conduction improvement layer. Figure 3The horizontal axis represents the number of cycles at different discharge rates, and the vertical axis represents the specific capacity, in units of mAh / g. In order to more intuitively distinguish between Comparative Example 1 and Examples 1 to 3, the lithium-ion battery vapor-deposited silicon-carbon negative electrode structures of lithium aluminum phosphate without, or with 2, 5, and 10 layers of sub-nanometer-scale ion conduction improvement layers are represented as ALD-undeposited, ALD-Li3PO4 / AlPO4-2 layers, ALD-Li3PO4 / AlPO4-5 layers, and ALD-Li3PO4 / AlPO4-10 layers.

[0103] For the carbon-silicon negative electrode structure including the ion conduction improvement layer in Examples 1 to 3, according to the BET data table in Table 1 and Figure 2 The SEM results show that, compared with the porous carbon substrate without lithium aluminum phosphate deposition, the specific surface area of ​​the porous carbon substrate decreases when the number of interface modification layers is 2, indicating that lithium aluminum phosphate is effectively deposited on the pores of the porous carbon through the ALD technology, thereby increasing the ion transmission channels. Figure 3 The battery rate performance test also shows that the polarization phenomenon in the electrochemical process has been effectively suppressed. When the number of interface modification layers is 5 and 10, the specific surface area is further reduced, which shows that lithium aluminum phosphate can still be effectively deposited on the surface of porous carbon through ALD technology, but this also leads to the compression of the space for subsequent silicon particles to be deposited, resulting in a decrease in the overall specific capacity of the silicon-carbon material. It can be seen that the carbon-silicon negative electrode structure containing an ion conduction improvement layer in Example 1 has good interface affinity between lithium aluminum phosphate and Si or C, which can enhance the bonding between Si and C, and increase a large number of electron transmission channels and ion transmission channels, thereby achieving the technical effect of preventing Si from falling off the conductive network and enhancing the ion transmission rate.

[0104] In summary, compared with Comparative Example 1, the lithium ion batteries made of the carbon-silicon negative electrode structure containing the ion conduction improvement layer in Examples 1 to 3 have a shortened polarization platform of the charging curve, and the polarization phenomenon in the electrochemical process is effectively suppressed; this shows that the addition of lithium phosphate, aluminum phosphate, and lithium aluminum phosphate can increase a large number of electron transmission channels and ion transmission channels, and solve the problem of low interface transmission efficiency between Si and carbon.

[0105] Table 1 BET data of different carbon-silicon anode structures

[0106]

[0107] It should be noted that the present invention mainly provides a porous carbon structure for depositing a sub-nanometer scale ion conduction improvement layer by atomic layer deposition, but the introduction of a sub-nanometer scale ion conduction improvement layer may also be achieved by vapor deposition, solution deposition, evaporation and other techniques.

[0108] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations of these embodiments are made without departing from the principles and spirit of the present invention, and still fall within the protection scope of the present invention.

Claims

1. A porous carbon silicon negative electrode structure, characterized in that: The porous carbon silicon negative electrode structure includes a porous carbon substrate, silicon particles and a sub-nanoscale ion conduction improvement layer in the middle layer, and the sub-nanoscale ion conduction improvement layer is coated on the surface of the porous carbon substrate; the sub-nanoscale ion conduction improvement layer includes silicon carbide, aluminum phosphide, aluminum nitride, aluminum oxide, lithium phosphate, aluminum phosphate, and lithium aluminum phosphate.

2. A porous carbon silicon negative electrode structure according to claim 1, characterized in that: The sub-nanometer scale ion conduction improving layer is lithium aluminum phosphate.

3. The method for preparing the porous carbon silicon negative electrode structure according to claim 2, characterized in that: The following steps are involved: S11: providing a porous carbon substrate; S12: introducing a gaseous precursor and depositing a lithium aluminum phosphate film on the surface of the porous carbon substrate by atomic layer deposition, specifically including steps S121 to S1211. In steps S121 to S1210, nitrogen is used as a carrier gas at a flow rate of 5 to 200 sccm: S121: Laying out base materials, laying out tert-butyl lithium in a tert-butyl lithium tank, laying out trimethyl phosphate in a trimethyl phosphate cylinder, laying out trimethyl aluminum in a trimethyl aluminum cylinder, and laying out a porous carbon substrate in a reaction chamber; S122: heating the equipment, heating the initial temperature of tert-butyl lithium to 120°C, and the initial temperature of trimethyl phosphate to 45°C; heating the initial temperature of the reaction chamber to 100-500°C, heating the initial temperature of the transport pipeline and the ALD pulse valve to 180°C, and evacuating the reaction chamber and the transport pipeline to a pressure of 5-500Pa; S123: After applying the lithium source and the ALD system is evenly heated, the ALD pulse valve at the tert-butyl lithium tank is opened for 300 to 3000 ms to allow the tert-butyl lithium to enter the reaction chamber, undergo self-saturated adsorption and exchange reaction with the surface of the substrate to be plated, and generate a lithium-substituted substrate; S124: cleaning the residual material, introducing an inert gas pulse into the reaction chamber to clean the tert-butyl lithium that has not reacted completely and the by-products generated by the reaction; S125: Reduction reaction, opening the ALD pulse valve at the trimethyl phosphate cylinder for 20 to 1000 ms, so that the trimethyl phosphate enters the reaction chamber in the gas phase, chemically adsorbs and reacts with the surface of the lithium-substituted base material, and generates a lithium phosphate thin film blank; S126: Cleaning the film, introducing an inert gas pulse into the reaction chamber to clean the phosphoric acid source that has not reacted completely and the byproducts generated by the reaction, and then generating a single-layer atomic layer deposited lithium phosphate film through self-saturation; S127: Open the ALD pulse valve at the trimethyl aluminum cylinder for 20 to 1000 ms to allow trimethyl aluminum to enter the reaction chamber in gas phase and chemically adsorb and react with the surface of the lithium phosphate film to generate an aluminum-based replacement base material; S128: Cleaning the membrane, introducing an inert gas pulse into the reaction chamber to clean the phosphoric acid source that has not reacted completely and the by-products generated by the reaction; S129: Reduction reaction, opening the ALD pulse valve at the trimethyl phosphate cylinder for 20 to 1000 ms, so that the trimethyl phosphate enters the reaction chamber in the gas phase, chemically adsorbs and reacts with the surface of the aluminum replacement base material, and generates a lithium aluminum phosphate thin film blank; S1210: Cleaning and film formation, introducing an inert gas pulse into the reaction chamber to clean the unreacted phosphoric acid source and the byproducts generated by the reaction, and then generating a double-layer atomic layer deposited lithium aluminum phosphate film through self-saturation; S13: performing multilayer deposition, repeating the process cycle of step S121 to step S1210 on the lithium aluminum phosphate thin film material obtained by the double-layer atomic layer deposition, and stacking another lithium aluminum phosphate thin film on the lithium aluminum phosphate thin film material, while controlling the total thickness of the lithium aluminum phosphate thin film to not more than 2 nm; S14: using the modified substrate material of S13 in a subsequent silicon deposition step to prepare a modified vapor-deposited silicon-carbon material.

4. The method for preparing a porous carbon silicon negative electrode structure according to claim 3, characterized in that: In S13, the total thickness of the lithium aluminum phosphate film is controlled to be no more than 1 nm.

5. The method for preparing a porous carbon silicon negative electrode structure according to claim 3, characterized in that: In steps S121 to S1210 , nitrogen is used as carrier gas with a flow rate of 5 to 100 sccm.

6. The method for preparing a porous carbon silicon negative electrode structure according to claim 3, characterized in that: In step S122, the initial temperature of the reaction chamber is heated to 150-300°C, and the reaction chamber and the transport pipeline are evacuated to a pressure of 10-200Pa.

7. The method for preparing a porous carbon silicon negative electrode structure according to claim 3, characterized in that: In step S123, the ALD pulse valve at the tert-butyl lithium tank is opened for 500 to 2000 ms.

8. The method for preparing a porous carbon silicon negative electrode structure according to claim 3, characterized in that: In step S125, the ALD pulse valve at the trimethyl phosphate cylinder is opened for 50 to 500 ms; in step S127, the ALD pulse valve at the trimethyl aluminum cylinder is opened for 50 to 500 ms; in step S129, the ALD pulse valve at the trimethyl phosphate cylinder is opened for 50 to 500 ms.

9. A battery, characterized in that: The battery comprises the porous carbon silicon negative electrode structure according to claim 1 or 2.

Citation Information

Patent Citations

  • Method for preparing lithium phosphate film through atomic layer deposition

    CN111304631A

  • Carbon-silicon negative electrode structure containing silicon-carbon bonding layer and preparation method of carbon-silicon negative electrode structure

    CN117712318A

  • Porous silicon carbon negative electrode material and preparation method thereof, negative electrode plate and battery

    CN118553900A

  • Lithium phosphate coated and modified silicon-carbon negative electrode material and preparation method thereof

    CN118983425A

  • Atomic layer deposition of metal phosphates and lithium silicates

    US20120276305A1

Cited By

  • Negative electrode material and preparation method thereof, secondary battery and electronic device

    CN119965252A

  • Silicon-carbon negative electrode material utilizing atomic layer deposition and preparation method of silicon-carbon negative electrode material

    CN120432511A

  • Preparation method of silicon-carbon negative electrode material, silicon-carbon negative electrode material and application of silicon-carbon negative electrode material

    CN120943254A

  • Silicon-carbon negative electrode material and preparation method thereof

    CN120978054A

  • Nano silicon / mesoporous carbon silicon carbon composite negative electrode material based on CVD (chemical vapor deposition), preparation method of nano silicon / mesoporous carbon silicon carbon composite negative electrode material and lithium ion battery

    CN122025610A